Composite electrode material based on MXene / NiCo2O4 and preparation method and application thereof

By uniformly loading NiCo2O4 nanospheres on the surface and between layers of the MXene layer, an efficient electron transport path was constructed, solving the problems of poor conductivity and volume expansion of NiCo2O4, and achieving high charge storage capacity and long cycle life of the supercapacitor.

CN121096793AInactive Publication Date: 2025-12-09ZHONGBEI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511646159.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-11
Publication Date
2025-12-09
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, NiCo2O4 has poor conductivity and volume expansion, resulting in poor rate performance and decreased cycle stability. MXene is easily oxidized and stacked, limiting the cycle stability of electrode materials. Weak interfacial contact leads to insufficient conductivity.

Method used

By employing an electrostatic self-assembly strategy, NiCo2O4 nanospheres are uniformly anchored on the surface and between layers of the MXene layer, forming a strong chemical bond, constructing an efficient electron transport path, suppressing the volume expansion of NiCo2O4, enhancing structural stability, and addressing the issues of poor conductivity and agglomeration by adjusting the ratio of NiCo2O4 to MXene.

Benefits of technology

It significantly improves the charge storage capacity and rate performance of supercapacitors, extends cycle life, and ensures good interfacial contact and electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121096793A_ABST
    Figure CN121096793A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical energy storage, and discloses a composite electrode material based on MXene / NiCo2O4 and a preparation method and application thereof, the preparation method comprises the following steps: step 1, preparation of MXene dispersion liquid: step 2, preparation of CTAB-NiCo2O4 powder; and 3, adding an MXene dispersion liquid into the obtained CTAB-NiCo2O4 powder, carrying out magnetic stirring, carrying out vacuum drying, and calcining to obtain the product. According to the invention, through an electrostatic self-assembly strategy, positively charged functional groups on the surface of MXene are utilized, positively charged Ni < 2 + > and Co < 2 + > are uniformly anchored on the surface of an MXene sheet layer and among the MXene sheet layers through electrostatic interaction, the electrochemical performance of the composite material is remarkably improved, and the composite material can be widely applied to supercapacitors.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the field of electrochemical energy storage technology, in particular to a composite electrode material based on MXene / NiCo2O4 and a preparation method and application thereof. BACKGROUND

[0002] The rapid development of high-performance portable electronic devices puts forward higher requirements for efficient and reliable energy storage technology. Supercapacitors have the advantages of high power density, fast charge and discharge, and long cycle life, but their low energy density limits their application. Transition metal oxide pseudocapacitive materials (such as NiCo2O4) have high theoretical capacity, but their intrinsic conductivity is poor, and volume expansion leads to poor rate performance and decreased cycle stability. In the prior art, carbon materials (such as graphene, carbon nanotubes) are used to composite NiCo2O4, which only partially improves the conductivity, but there are still core problems such as weak interface contact, insufficient carbon-based conductivity, and poor interface stability. MXene, as a new conductive two-dimensional material, has high conductivity, flexibility and rich surface functional groups, but its characteristics of easy oxidation and easy stacking limit the cycle stability as an electrode material.

[0003] Therefore, how to improve the performance of electrode materials to improve the comprehensive performance of supercapacitors is still a technical problem to be solved in the field of electrochemical energy storage. SUMMARY

[0004] In order to solve the above technical problems, the application provides a composite electrode material based on MXene / NiCo2O4 and a preparation method and application thereof, so as to significantly improve the charge storage capacity of the capacitor and obtain better electrochemical performance.

[0005] In order to solve the above technical problems, the application adopts the technical scheme that a preparation method of a composite electrode material based on MXene / NiCo2O4 comprises the following steps: Step 1: Preparation of MXene dispersion liquid: Under water bath conditions, LiF is added to the prepared hydrochloric acid and stirred until it is light yellow, then MAX phase material is added to the solution in multiple times and stirred to completely etch the Al layer in the middle, and then the solution is subjected to argon aeration, ice bath ultrasonic treatment after multiple centrifugation until the supernatant PH>6, to obtain a single-layer MXene dispersion liquid; Step 2: Preparation of CTAB-NiCo2O4 powder: CoCl2·6H2O, NiCl2·6H2O, urea and NH4F were added into deionized water, and magnetic stirring was performed until the solution appeared light pink; the solution was transferred into a hydrothermal reactor, and after the reaction was completed, the precipitate was repeatedly washed with water and anhydrous ethanol, and then the precipitate was added into the prepared CTAB solution and magnetic stirring was performed, and then the obtained precipitate was transferred into an annealing furnace for calcination to obtain CTAB-NiCo2O4 powder; Step 3: MXene dispersion liquid was added into the obtained CTAB-NiCo2O4 powder, and after magnetic stirring, vacuum drying was performed, and then calcination was performed to obtain the product.

[0006] In step 3, the mass ratio of CTAB-NiCo2O4 powder to MXene in the MXene dispersion liquid is 2:1-2:4.

[0007] In step 3, the mass ratio of CTAB-NiCo2O4 powder to MXene in the MXene dispersion liquid is 2:3.

[0008] In step 1, the water bath temperature is 45℃, the stirring time after adding the MAX phase material is 36-60h, the centrifugal speed is 3500rpm, and the ultrasonic time is 1h.

[0009] In step 1, 3.2g of LiF was added into the prepared 40ml of 9M hydrochloric acid, and then 2g of the MAX phase material was added into the solution in 10 times, 0.2g each time.

[0010] In step 2, the molar ratio of CoCl2·6H2O, NiCl2·6H2O, urea and NH4F added is 5:2.5:9:22.5.

[0011] In step 2, the reaction condition in the hydrothermal reactor is 130℃ for 8h; the mass concentration of the CTAB solution is 0.1%, the magnetic stirring time is 24h, and the calcination condition is: the temperature is increased at a rate of 5℃ per minute until 400℃, and then the temperature is kept constant for two hours.

[0012] In step 3, after magnetic stirring for 24h, vacuum drying is performed at 60℃ for 8h, and then the temperature is increased at a rate of 5℃ per minute until 400℃, and then the temperature is kept constant for two hours.

[0013] In addition, the application also provides a MXene / NiCo2O4-based composite electrode material, which is prepared based on the preparation method of the MXene / NiCo2O4-based composite electrode material.

[0014] In addition, the application further provides application of the composite electrode material based on MXene / NiCo2O4 in a supercapacitor, and the supercapacitor takes the composite electrode material as a positive electrode, takes activated carbon as a negative electrode, and takes a cellulose diaphragm as a separator between the positive electrode and the negative electrode.

[0015] Compared with the prior art, the application has the following beneficial effects: 1. The application provides a composite electrode material based on MXene / NiCo2O4 and a preparation method and application thereof. 2+ , Co 2+ The NiCo2O4 is uniformly anchored on the surface and between layers of MXene sheets through electrostatic interaction, forms a strong chemical bond, is uniformly distributed in the form of nanospheres in the composite material, and is embedded in the flexible conductive network skeleton of MXene. 2. In the application, the flexible layered structure of MXene effectively inhibits the volume expansion of NiCo2O4 in the repeated charging and discharging process, prevents particle pulverization and agglomeration, enhances the structural stability, and prolongs the cycle life. 3. In the application, the strong interaction between the functional groups on the surface of MXene and NiCo2O4 ensures firm interface contact, avoids the poor contact problem of conventional physical mixing, and the double-layer capacitor type MXene and the pseudo-capacitor type NiCo2O4 synergistically act, complement each other through energy storage mechanisms, and can significantly improve the overall charge storage capacity. 4. In the application, by regulating and optimizing the ratio of NiCo2O4 and MXene, the problems of poor conductivity and agglomeration caused by excessive MXene self-stacking and blocking ion channels or excessive NiCo2O4 are successfully solved, and the best electrochemical performance is obtained.

[0016] In summary, the electrode material has outstanding electrochemical performance and can be widely applied in supercapacitors. BRIEF DESCRIPTION OF DRAWINGS

[0017] Figure 1 The SEM cross-section electron microscope graph of the composite material obtained when the composite ratio of NiCo2O4 and MXene in the embodiments of the application is 2:3 is observed, and it is observed that the NiCo2O4 particles are uniformly loaded between the MXene layers and on the surface. Figure 2For the current-voltage curve comparison chart of NiCo2O4 and MXene in different composite ratios in the embodiment of the application, it is observed that the area surrounded by the curve of the composite ratio of MXene and NiCo2O4 at 2:3 is the largest, and the specific capacitance is the largest; Figure 3 For the voltage-time curve of NiCo2O4 and MXene in different composite ratios at a current density of 1A / g in the embodiment of the application, it is observed that the charge-discharge time of the composite ratio of NiCo2O4 and MXene at 2:3 is the longest, and the specific capacitance is the largest; Figure 4 For the current-voltage curve of the composite material (N2M3) obtained when the composite ratio of NiCo2O4 and MXene is 2:3 in the embodiment of the application, and the single NiCo2O4 material (NCO) and the single MXene material, it is illustrated that the electrochemical performance of the composite material of the application is more prominent; Figure 5 For the impedance spectrum of the composite material (N2M3) obtained when the composite ratio of NiCo2O4 and MXene is 2:3 in the embodiment of the application, and the single NiCo2O4 material (NCO) and the single MXene material, it is observed that the radius of the high-frequency region of the N2M3 composite material is smaller, the slope of the low-frequency region is larger, the resistance is lower, and the charge transmission rate is faster; Figure 6 For the charge-discharge curve of the asymmetric supercapacitor (ASC) assembled by the composite material N2M3 obtained when the composite ratio of NiCo2O4 and MXene is 2:3 in the embodiment of the application and AC (activated carbon) after 10,000 cycles, the capacitance retention rate is 83.7% of the initial value. DETAILED DESCRIPTION

[0018] To make the purpose, technical scheme and advantages of the embodiments of the application clearer, the technical scheme in the embodiments of the application will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the application, rather than all the embodiments. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the application.

[0019] Embodiment one The embodiment one of the application provides a preparation method of a composite electrode material based on MXene / NiCo2O4, which comprises the following steps: Step 1: Preparation of MXene dispersion liquid LiF was added into the prepared hydrochloric acid under water bath condition and stirred until the solution was light yellow. Then, MAX phase material was added into the solution in multiple times and stirred to completely etch the middle Al layer. After multiple centrifugations until the supernatant PH was greater than 6, the solution was subjected to argon gas aeration, ice bath ultrasonic treatment, and then a single-layer MXene dispersion was obtained. The concentration of the single-layer MXene dispersion was diluted to 2 mg / ml.

[0020] In the step 1, the water bath temperature was 45℃, the MAX phase material was added and stirred for 36-60h, the centrifugation rate was 3500rpm, and the ultrasonic treatment time was 1h.

[0021] In the step 1, 3.2g of LiF was added into the prepared 40ml of 9M hydrochloric acid, and then 2g of MAX phase material was added into the solution in 10 times, 0.2g each time.

[0022] In the step 1, the added MAX phase material was Ti3AlC2.

[0023] Step 2: Preparation of CTAB-NiCo2O4 powder: CoCl2·6H2O, NiCl2·6H2O, urea and NH4F were added into deionized water and magnetically stirred until the solution was light pink. The solution was transferred into a hydrothermal reactor, and after the reaction was completed, the precipitate was repeatedly washed with water and anhydrous ethanol. The precipitate was added into a prepared CTAB (cetyltrimethylammonium bromide) solution and magnetically stirred. Then, the washed precipitate was transferred into an annealing furnace to obtain the CTAB-NiCo2O4 powder.

[0024] In the step 2, the molar ratio of CoCl2·6H2O, NiCl2·6H2O, urea and NH4F added was 5:2.5:9:22.5.

[0025] Specifically, in the step 2, 5mmol of CoCl2·6H2O, 2.5mmol of NiCl2·6H2O, 9mmol of urea and 22.5mmol of NH4F were added into 30ml of deionized water. After magnetically stirring until the solution was light pink, the solution was transferred into a 100ml PTFE hydrothermal reactor and reacted at 130℃ for 8 hours. After the reaction was completed, the precipitate was repeatedly washed with water and anhydrous ethanol. The precipitate was added into a prepared 50ml CTAB solution with a mass concentration of 0.1% and magnetically stirred for 24 hours. Then, the washed precipitate was transferred into an annealing furnace to obtain the required CTAB-NiCo2O4 powder. The CTAB-NiCo2O4 powder represents the NiCo2O4 powder after surfactant CTAB and calcination treatment.

[0026] Step 3: Add MXene dispersion liquid to the obtained CTAB-NiCo2O4 powder, and then perform vacuum drying after magnetic stirring, and then perform calcination to obtain the product.

[0027] Specifically, in step 3, the mass ratio of CTAB-NiCo2O4 powder to MXene in the MXene dispersion liquid is 2:3.

[0028] Specifically, in step 3, 50 mg of CTAB-NiCo2O4 powder is added to a beaker, and then 37.5 ml of MXene dispersion liquid with a concentration of 2 mg / ml is added. After magnetic stirring for 24 hours, vacuum drying is performed at 60℃ for 8 hours, and then calcination is performed at a temperature increasing rate of 5℃ per minute until 400℃ is kept constant, and then calcination is performed for two hours. The sample is denoted as N2M3.

[0029] Figure 1 The SEM cross-sectional electron microscope image of the composite material prepared in this embodiment is shown, and it is observed that the NiCo2O4 particles are uniformly loaded between the MXene layers and the surface.

[0030] Embodiment two Embodiment two of the present application provides a preparation method of a composite electrode material based on MXene / NiCo2O4. The preparation process is the same as that of embodiment one, and the only difference is that in step 3 of this embodiment, the mass ratio of CTAB-NiCo2O4 powder to MXene in the MXene dispersion liquid is 1:1, and the prepared sample is denoted as N1M1.

[0031] Embodiment three Embodiment three of the present application provides a preparation method of a composite electrode material based on MXene / NiCo2O4. The preparation process is the same as that of embodiment one, and the only difference is that in step 3 of this embodiment, the mass ratio of CTAB-NiCo2O4 powder to MXene in the MXene dispersion liquid is 1:2, and the prepared sample is denoted as N1M2.

[0032] Embodiment four Embodiment four of the present application provides a preparation method of a composite electrode material based on MXene / NiCo2O4. The preparation process is the same as that of embodiment one, and the only difference is that in step 3 of this embodiment, the mass ratio of CTAB-NiCo2O4 powder to MXene in the MXene dispersion liquid is 2:1, and the prepared sample is denoted as N2M1.

[0033] Embodiment five Example five of the present application provides a preparation method of a composite electrode material based on MXene / NiCo2O4. The preparation process is the same as that of example one, the only difference is that in step 3 of the present example, the mass ratio of CTAB-NiCo2O4 powder to MXene in the MXene dispersion is 3:2. The prepared sample is denoted as N3M2.

[0034] Comparative example 1 The CTAB-NiCo2O4 obtained in step 2 of example one of the present application is used as an electrode material.

[0035] Comparative example 2 The MXene dispersion obtained in step 1 of example one of the present application is centrifuged to collect the precipitate, which is vacuum dried at 60°C for 12 hours. The obtained sample is used as an electrode material and is denoted as MXene.

[0036] Example six Example six of the present application provides a composite electrode material based on MXene / NiCo2O4, which is prepared based on the preparation method of the composite electrode material based on MXene / NiCo2O4 described in examples one to five. In the composite electrode material, NiCo2O4 particles are uniformly loaded between the layers and on the surface of MXene.

[0037] Example seven Example seven of the present application provides an electrode preparation method. A piece of foamed nickel (1×2 cm 2 ) is placed in an ethanol and water solution (1:1) for ultrasonic treatment for 30 minutes. The cleaned foamed nickel is vacuum dried at 60°C for 6 hours. The active material, conductive carbon black and polyvinylidene fluoride (PVDF) are mixed in N-methyl-2-pyrrolidone (NMP) at a mass ratio of 8:1:1 for stirring for 6 hours to form a slurry, which is uniformly coated on the foamed nickel. The loading of the active material on the foamed nickel is about 1 mg / cm 2 . Finally, the coated foamed nickel is vacuum dried at 80°C for 12 hours to obtain a working electrode.

[0038] The active material is the electrode material prepared in examples one to five, and comparative examples 1 and 2.

[0039] The electrochemical performance of different electrodes prepared in example seven is tested. During the test, a CHI660E electrochemical workstation is used to perform a three-electrode system. The test content includes cyclic voltammetry (CV), galvanostatic charge and discharge (GCD) and electrochemical impedance spectroscopy (EIS). A Hg / HgO electrode is used as a reference electrode, a Pt electrode is used as a counter electrode, and a 2M KOH solution is used as an electrolyte. Based on the galvanostatic charge and discharge curve, the mass specific capacitance can be calculated, and the calculation formula is as follows: (1) In the formula, represents the mass specific capacitance of the electrode, I is the current intensity (A), m1 is the active load mass of the electrode (g), ΔV is the voltage window (V), and Δt is the discharge time (s).

[0040] Figure 2 The current-voltage curve comparison diagram of MXene and NiCo2O4 at different composite ratios at a scan rate of 100 mV / s is shown, and it is observed that the area surrounded by the curve at the composite mass ratio of NiCo2O4 and MXene is the largest, and the specific capacitance is the largest.

[0041] Figure 3 The voltage-time curve of MXene and NiCo2O4 at different composite ratios at a current density of 1 A / g is shown, and it is observed that the charge-discharge time is the longest and the specific capacitance is the largest at the composite mass ratio of NiCo2O4 and MXene is 2:3.

[0042] Figure 4 The current-voltage curve of N2M3, NiCo2O4 and MXene prepared by example one, comparative example 1 and comparative example 2 respectively is shown, which shows that the electrochemical performance of the composite material obtained by compounding the two materials in the embodiment of the application is more prominent.

[0043] Figure 5 The impedance spectrum of N2M3, NiCo2O4 and MXene prepared by example one, comparative example 1 and comparative example 2 respectively is shown, and it is observed in the figure that the radius of the high-frequency region of the electrode corresponding to the N2M3 material is smaller, the slope of the low-frequency region is larger, the resistance is lower, and the charge transfer rate is faster.

[0044] Example eight The embodiment eight of the application provides an application of a composite electrode material based on MXene / NiCo2O4 in a supercapacitor, wherein the composite electrode material is used as a positive electrode, activated carbon is used as a negative electrode, and a cellulose diaphragm is used to insulate between the positive and negative electrodes.

[0045] In this embodiment, the N2M3 material obtained in example one is made into a positive electrode, commercial activated carbon (AC) is made into a negative electrode, a cellulose diaphragm is used to insulate between the positive and negative electrodes, 3M concentration KOH is used as an electrolyte, and an asymmetric supercapacitor (ASC) is assembled in a CR2032 button cell shell. A series of electrochemical performance tests are carried out on the asymmetric supercapacitor using a double electrode system, including cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) and electrochemical impedance (EIS), and the cycle stability of the asymmetric supercapacitor is evaluated by a new Wei test instrument CT-4008T.

[0046] In the test, the voltage window interval of the asymmetric supercapacitor is 0-1.6V, the frequency range of electrochemical impedance spectroscopy (EIS) test is 0.01Hz to 10MHz, and the amplitude is 5mV. The specific capacitance of the asymmetric supercapacitor is calculated by formula (2)-(4) C 2, energy density E and power density P : ; (2) ; (3) ; (4) wherein I, Δt, and ΔV represent current intensity, discharge time, common load mass (g) of positive and negative electrodes, and voltage window (V), respectively. The energy density (Wh / kg) and power density (W / kg) are calculated based on the GCD results at different current densities.

[0047] As Figure 6 shown, 10,000 GCD cycles are performed at a specific current density, and the capacity retention rate of the asymmetric supercapacitor is calculated to be 83.7% after 10,000 cycles.

[0048] Finally, it should be noted that: the above embodiments are only used to illustrate the technical solutions of the present application, but not to limit them; although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that: it can still modify the technical solutions recorded in the foregoing embodiments, or make equivalent replacement for part or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a composite electrode material based on MXene / NiCo2O4, characterized in that, Includes the following steps: Step 1: Preparation of MXene dispersion: Under water bath conditions, LiF was added to the prepared hydrochloric acid and stirred until pale yellow. Then, the MAX phase material was added to the solution in multiple batches and stirred to completely etch the intermediate Al layer. After multiple centrifugations until the pH of the supernatant was greater than 6, the solution was purged with argon gas and sonicated in an ice bath to obtain a monolayer MXene dispersion. Step 2: Preparation of CTAB-NiCo2O4 powder: Add CoCl2·6H2O, NiCl2·6H2O, urea and NH4F to deionized water and stir magnetically until the solution turns light pink. Transfer the solution to a hydrothermal reactor. After the reaction is complete, wash the precipitate repeatedly with water and anhydrous ethanol. Add the precipitate to the prepared CTAB solution and stir magnetically. Then transfer the precipitate to an annealing furnace to calcine and obtain CTAB-NiCo2O4 powder. Step 3: Add MXene dispersion to CTAB-NiCo2O4 powder, stir magnetically, vacuum dry, and then calcine to obtain the product.

2. The method for preparing a composite electrode material based on MXene / NiCo2O4 according to claim 1, characterized in that, In step 3, the mass ratio of CTAB-NiCo2O4 powder to MXene in the MXene dispersion is 2:1 to 2:

4.

3. The method for preparing a composite electrode material based on MXene / NiCo2O4 according to claim 1, characterized in that, In step 3, the mass ratio of CTAB-NiCo2O4 powder to MXene in the MXene dispersion is 2:

3.

4. The method for preparing a composite electrode material based on MXene / NiCo2O4 according to claim 1, characterized in that, In step 1, the water bath temperature is 45℃, the MAX phase material is added and stirred for 36-60 hours, the centrifugation rate is 3500 rpm, and the ultrasonic time is 1 hour.

5. The method for preparing a composite electrode material based on MXene / NiCo2O4 according to claim 1, characterized in that, In step 1, 3.2g of LiF is added to 40ml of prepared 9M hydrochloric acid, and then 2g of MAX phase material is added to the solution in 10 portions, 0.2g each time.

6. The method for preparing a composite electrode material based on MXene / NiCo2O4 according to claim 1, characterized in that, In step 2, the molar ratio of CoCl2·6H2O, NiCl2·6H2O, urea and NH4F is 5:2.5:9:22.

5.

7. The method for preparing a composite electrode material based on MXene / NiCo2O4 according to claim 1, characterized in that, In step 2, the reaction conditions in the hydrothermal reactor are: reaction at 130°C for 8 hours; the mass concentration of the CTAB solution is 0.1%; the magnetic stirring time is 24 hours; and the calcination conditions are: heating at a rate of 5°C per minute until reaching 400°C, and then maintaining a constant temperature for calcination for two hours.

8. The method for preparing a composite electrode material based on MXene / NiCo2O4 according to claim 1, characterized in that, In step 3, after magnetic stirring for 24 hours, the product is vacuum dried at 60°C for 8 hours, then heated to 400°C at a rate of 5°C per minute, and then calcined at a constant temperature for two hours.

9. A composite electrode material based on MXene / NiCo2O4, characterized in that, The composite electrode material based on MXene / NiCo2O4 was prepared according to the preparation method of claim 1, wherein NiCo2O4 particles are uniformly loaded in the MXene interlayer and on the surface.

10. The application of the MXene / NiCo2O4-based composite electrode material in a supercapacitor according to claim 9, characterized in that, The supercapacitor uses the composite electrode material as the positive electrode and activated carbon as the negative electrode, with a cellulose membrane separating the positive and negative electrodes.

Citation Information

Patent Citations

  • Preparation method and application of foam nickel loaded MnCo2O4.5 / MXene composite nano material

    CN112233912A